Business Planning and Strategic Development of CV Madani Konsultan: A Model for MSME Advisory Services - Sinuraya, Fajar Syah Faizal; Kaniawati, Keni (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Siliwangi, 2025)
This study aims to develop a comprehensive business plan and strategic model for CV Madani Konsultan as an emerging MSME advisory service designed to strengthen the credit readiness of micro, small, and medium enterprises in Priangan Timur. The research adopts a qualitative descriptive approach supported by document analysis, interviews, and field observations to explore MSME challenges in accessing formal financing. Four analytical frameworks were integrated, namely Design Thinking to identify user needs and pain points, SWOT analysis to assess internal and external conditions, the Timmons Model to evaluate the alignment of opportunity, team, and resources, and the Business Model Canvas to structure a viable and sustainable business model.The results show that CV Madani Konsultan operates within a favorable external environment and possesses strong internal capabilities, reflected in EFAS and IFAS scores of 3.73 and 3.64 respectively. The business demonstrates financial feasibility with a positive NPV, an IRR of 13.04 percent, and a payback period of 4.6 years. The strategic analysis places the firm in the aggressive growth quadrant, indicating high readiness for expansion through digital service development, strengthened partnerships with financial institutions, and targeted financial literacy programs for MSMEs. The study concludes that CV Madani Konsultan is market-ready, operationally feasible, and strategically positioned to contribute to financial inclusion and MSME professionalization in the region.